MIMO Systems in a Composite Fading and Generalized Noise Scenario: A Review - Tiwari, Keerti (Recent Patents on Engineering, 2020)
Multiple-Input Multiple-Output (MIMO) systems have been endorsed to enable future wireless communication requirements. The efficient system designing appeals an appropriate channel model that considers all the dominating effects of the wireless environment. Therefore, some complex or less analytically acquiescent composite channel models have been proposed typically for Single-Input Single-Output (SISO) systems. These models are explicitly employed for mobile applications, though, we need a specific study of a model for the MIMO system which can deal with radar clutters and different indoor/outdoor and mobile communication environments. Subsequently, the performance enhancement of the MIMO system is also required in such a scenario. The system performance enhancement can be examined by low error rate and high capacity using spatial diversity and spatial multiplexing respectively. Furthermore, for a more feasible and practical system modeling, we require a generalized noise model along with a composite channel model. Thus, all the patents related to MIMO channel models are revised to achieve the nearoptimal system performance in a real-world scenario. This review paper offers the methods to improve MIMO system performance in less and severe fading as well as shadowing environment and focused on a composite Weibull-gamma fading model. The development is the collective effects of selecting the appropriate channel models, spatial multiplexing/detection, and spatial diversity techniques both at the transmitter and the receivers in the presence of arbitrary noise.
Keywords: MIMO channel